PEMASARAN KAIN TENUN DI KELOMPOK TENUN LEMBANG KOLE BARABATU KABUPATEN TANA TORAJA - Daeng Toto, Herenal; -, Fatmasari; Bahtiar, Akbar; Muslaini, Fadel (Unit Publikasi dan Jurnal Sekolah Tinggi Ilmu Ekonomi Tri Dharma Nusantara Makassar, 2022)
This digital marketing training activity aims to provide an understanding of optimizing the use of social media as a marketing medium. The participants involved in this digital marketing workshop consisted of 8 people who were woven fabric craftsmen in Lembang Kole Barabatu, Tana Toraja Regency. The material presented in the implementation of this community service focused on discussions related to